Economic Evaluation of Dapagliflozin in the Treatment of Patients With Heart Failure: A Systematic Review - Wu, Meiyu; Qin, Shuxia; Wang, Liting; Tan, Chongqing; Peng, Ye; Zeng, Xiaohui; Luo, Xia; Yi, Lidan; Wan, Xiaomin (Frontiers in Pharmacology, 2022)
Objective: The objective of this study is to systematically review the economic evaluations of dapagliflozin in the treatment of patients with heart failure (HF). and describe their general and methodological features Methods: PubMed, Website Of Science, Embase, The Cochrane Library, ScienceDirect, CNKI, and Wanfang databases were searched to collect relevant studies and the retrieval time ended on October 31.2021. Basic characteristics, methods, and main results were extracted and analyzed systematically. Result: A total of 8 studies were identified and the overall quality was accepted, which were performed in nine developed countries (Austria, America, Korea, Japan, Singapore, Spanish, Germany, UK) and three developing countries (Philippines, Thailand, China). With the exception of the Philippines, the remaining countries considered that dapagliflozin was cost-effective. In the analyses of all included studies, the incremental cost-effectiveness ratios were most sensitive to the cost of dapagliflozin, cardiovascular mortality, the duration of dapagliflozin effectiveness, and the probability of HF hospitalization. Conclusion: Dapagliflozin in the treatment of patients with heart failure with reduced ejection fraction was considered cost-effective. Further studies are needed to evaluate the comprehensive value of dapagliflozin on HF.